A systematic review of the barcoding strategy that contributes to COVID-19 diagnostics at a population level - Chen, Heng-Chang (Frontiers in Molecular Biosciences, 2023)
The outbreak of SARS-CoV-2 has made us more alert to the importance of viral diagnostics at a population level to rapidly control the spread of the disease. The critical question would be how to scale up testing capacity and perform a diagnostic test in a high-throughput manner with robust results and affordable costs. Here, the latest 26 articles using barcoding technology for COVID-19 diagnostics and biologically-relevant studies are reviewed. Barcodes are molecular tags, that allow proceeding an array of samples at once. To date, barcoding technology followed by high-throughput sequencing has been made for molecular diagnostics for SARS-CoV-2 infections because it can synchronously analyze up to tens of thousands of clinical samples within a short diagnostic time. Essentially, this technology can also be used together with different biotechnologies, allowing for investigation with resolution of single molecules. In this Mini-Review, I first explain the general principle of the barcoding strategy and then put forward recent studies using this technology to accomplish COVID-19 diagnostics and basic research. In the meantime, I provide the viewpoint to improve the current COVID-19 diagnostic strategy with potential solutions. Finally, and importantly, two practical ideas about how barcodes can be further applied in studying SARS-CoV-2 to accelerate our understanding of this virus are proposed.